2014
DOI: 10.1371/journal.pone.0103715
|View full text |Cite
|
Sign up to set email alerts
|

Community-Associated Methicillin-Resistant Staphylococcus aureus Clonal Complex 80 Type IV (CC80-MRSA-IV) Isolated from the Middle East: A Heterogeneous Expanding Clonal Lineage

Abstract: BackgroundThe emergence of community-associated methicillin resistant Staphylococcus aureus (CA-MRSA) has caused a change in MRSA epidemiology worldwide. In the Middle East, the persistent spread of CA-MRSA isolates that were associated with multilocus sequence type (MLST) clonal complex 80 and with staphylococcal cassette chromosome mec (SCCmec) type IV (CC80-MRSA-IV), calls for novel approaches for infection control that would limit its spread.Methodology/Principal FindingsIn this study, the epidemiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 64 publications
3
29
1
Order By: Relevance
“…Despite this designation, they are widely distributed in the Middle East, including Egypt. The 3 CC80-MRSA-IV isolates identified in the course of the current study all carried aphA3 and sat in addition to PVL, which is characteristic for this strain, as well as etD + edinB [1, 33]. Overall, a number of different virulence genes were detected among the isolates in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Despite this designation, they are widely distributed in the Middle East, including Egypt. The 3 CC80-MRSA-IV isolates identified in the course of the current study all carried aphA3 and sat in addition to PVL, which is characteristic for this strain, as well as etD + edinB [1, 33]. Overall, a number of different virulence genes were detected among the isolates in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Nikolaras et al showed that 8% of MRSA strains isolated from bloodstream infections were assigned to MRSA-ST80 clone [77]. In a collection of 94 MRSA-ST80 strains isolated in Lebanon and Jordan, 56% of these isolates were associated with SSTIs, 15% with respiratory tract infections, and 9% with bacteremia [115]. Djahmi et al reported MRSA-ST80 PVL+ from inpatients with infected diabetic foot ulcers, requiring amputation (even if the link between these amputations and the presence of the clone was not determined) [35].…”
Section: Virulence Of Mrsa-st80mentioning
confidence: 99%
“…These bacteria are the most frequent agents in the community and hospitals. Communityassociated methicillin-resistant S. aureus (CA-MRSA) distribution has changed globally (5,6).…”
Section: Introductionmentioning
confidence: 99%